The power of RTI and reading profiles a blueprint for solving reading problems - Spear-Swerling, Louise (Paul H. Brookes Publishing Co., 2015)
"The reading problems addressed in the book move beyond those associated with disabilities such as dyslexia or high-functioning autism. The author addresses experientially based reading difficulties caused by inadequate instruction or limited exposure to academic language/literacy. Unlike other books on response to intervention (RTI), this book presents an argument for using RTI as a method of identification as well as intervention in combination with individual students' reading profiles. The case studies and practical examples cover a broad range of reading problems (not only learning disabilities) to help make research findings applicable to a multidisciplinary audience, especially practitioners"--Provided by publisher.